Pelatihan Penyusunan Laporan Keuangan Berbasis Digital Pada Usaha Umkm Pabrik Kerupuk Dua Putra Bengkulu - Hidayah, Nenden Restu; Galung, Mia Margareta Huta (Jurnal Dehasen Mengabdi, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the economy of a country. In Indonesia, MSMEs are the backbone of the economy with a significant contribution to economic growth, job creation and poverty alleviation. The Bengkulu Dua Putra Kerupuk Factory is an MSME engaged in the production and sale of crackers. This factory has the need to compile accurate financial reports and the training activity "Digital-Based Financial Reports on the UMKM Business of the Bengkulu Dua Putra Kerupuk Factory" is a program designed to provide an understanding and skills to MSME business actors at the Bengkulu Dua Putra Cracker Factory in compiling financial reports using digital technology. Training in preparing digital-based financial reports is very important for MSME businesses such as the Bengkulu Dua Putra Crackers Factory to improve efficiency and accuracy in financial management.